Coronary Artery Ectasia Are Frequently Observed in Patients With Bicuspid Aortic Valves With and Without Dilatation of the Ascending Aorta. (October 2016) - Meindl, Christine; Achatz, Birgit; Huber, Deborah; Baessler, Andrea; Hubauer, Ute; Meisinger, Christa; Hengstenberg, Christian; Erdmann, Jeanette; Buchner, Stefan; Maier, Lars; Schunkert, Heribert; Debl, Kurt; et al.
Abstract : Background—: The presence of coronary artery ectasia (CAE) is influenced by genetic factors and related to the presence of aneurysms in other vascular beds. Bicuspid aortic valve (BAV) disease is frequently accompanied by ascending aortic aneurysm. Because the aortic valve and the proximal parts of the coronary arteries share a common embryonic origin, we hypothesized that CAE is associated with BAV disease. Methods and Results—: One hundred seventy-seven patients with suspected aortic valve disease (n=94 BAV, n=83 tricuspid aortic valve) underwent both cardiac magnetic resonance imaging and coronary angiography. To confirm the association of CAE with BAV, the frequency of CAE was evaluated in an in-house BAV registry (n=600, n=231 with available coronary angiogram) and compared with the frequency of CAE in the German Myocardial Infarction (MI) Family Study, in which the heritability of CAE was formerly established (n=899). Furthermore, the frequency of CAE was investigated in an observational registry of real-life patients undergoing coronary angiography for clinically indicated reasons (n=3.097) and in a subgroup of the KORA MI study (Cooperative Health Research in the Region of Augsburg), which is a population-based MI registry (n=403). Compared with tricuspid aortic valve disease, CAE occurred more than twice as frequently in cardiac magnetic resonance–confirmed BAV disease (17% versus 44%; P <0.0001) and CAE was observed similarly often in subjects with BAV with (37%) and without (54%, P =0.11) ascending aortic pathology. The common appearance of CAE in patients with BAV could be independently confirmed in the BAV registry (frequency 37%), whereas CAE was found less frequently in family history of positive MI patients (21%), sporadic MI without familial disposition (10%), and rarely in unrelated real-life catheterization patients (6%). Conclusions—: To our knowledge, our data show for the first time that ectatic coronary artery disease is a common appearance of BAV disease with and without ascending aortic ectasia.